MicroRNA sponges: Progress and possibilities - Ebert, Margaret S. (Cold Spring Harbor Laboratory Press, 2010)
The microRNA (miRNA) “sponge” method was introduced three years ago as a means to create continuous miRNA loss of function in cell lines and transgenic organisms. Sponge RNAs contain complementary binding sites to a miRNA of interest, and are produced from transgenes within cells. As with most miRNA target genes, a sponge's binding sites are specific to the miRNA seed region, which allows them to block a whole family of related miRNAs. This transgenic approach has proven to be a useful tool to probe miRNA functions in a variety of experimental systems. Here we will discuss the ways sponge and related constructs can be optimized and review recent applications of this method with particular emphasis on stable expression in cancer studies and in transgenic animals.